The effect of using tuff on strength of concrete in hot weather - Ibrahim, Ahmad J. (Al-Mukhtar Journal of Sciences, 2010)
This paper investigates the effect of hot weather condition on the flexural and compressive strength of concrete, containing different percentages of ground tuff as partial replacement of cement used in concrete mixes. The results indicate that using ground tuff as a partial replacement of cement (up to 20%) for concrete cast and curded in hot weather decreases deficiency of influence of high temperature on compressive strength.